APPLICATION OF INFORMATION TECHNOLOGY THROUGH DESKTOP-BASED APPLICATIONS TO HELP THE OPERATIONAL PRODUCTIVITY OF THE UMKM “KOPI PINGGIR KALI” (KPK) - Ibad, Sholihul (Jurnal Disprotek, 2025)
This research describes the creation of a desktop-based cash register application that aims to increase operational productivity at MSMEs "Kopii Pingir Kali" (KPK) located in Boto Village, Semanding District, Tuban Regency. This application is designed to solve various problems faced by MSMEs such as: Examples include manual transaction entry, which is time-consuming and error-prone, as well as difficulty tracking daily inventory and revenue. Using the waterfall software development methodology, this cashier application was developed with key features such as sales recording, inventory management, daily sales report, and food menu data management. The system was tested based on simulated transactions and user feedback and showed improved efficiency in transaction processing and report management. The introduction of this application aims to enable MSMEs "Kopi Pinggir Kali" (KPK) to improve the accuracy of transaction recording, speed up the sales process and provide more accurate and timely reports. The results of this study show that the use of information technology in MSME operations can have a positive impact on business productivity and efficiency, and provide MSMEs with practical solutions to overcome daily operational challenges.PENERAPAN TEKNOLOGI INFORMASI MELALUI APLIKASI BERBAIS DEKSTOP UNTUK MEMBANTU PRODUKTIFITAS OPERASIONAL UMKM “KOPI PINGGIR KALI” (KPK)Penelitian ini menjelaskan tentang pembuatan aplikasi mesin kasir berbasis desktop yang bertujuan untuk meningkatkan produktivitas operasional pada UMKM “Kopii Pingir Kali” (KPK) yang berlokasi di Desa Boto, Kecamatan Semanding, Kabupaten Tuban. Aplikasi ini dirancang untuk menyelesaikan berbagai permasalahan yang dihadapi UMKM seperti: Contohnya termasuk entri transaksi manual, yang memakan waktu dan rawan kesalahan, serta kesulitan  melacak inventaris dan pendapatan harian. Dengan menggunakan metodologi pengembangan perangkat lunak air terjun, aplikasi kasir ini dikembangkan dengan fitur-fitur utama seperti pencatatan penjualan, pengelolaan inventaris, laporan penjualan harian, dan pengelolaan data menu makanan. Sistem diuji berdasarkan simulasi transaksi dan umpan balik pengguna meningkatkan akurasi pencatatan transaksi, mempercepat proses penjualan dan memberikan laporan yang lebih akurat dan tepat waktu. Hasil penelitian ini menunjukkan bahwa penggunaan teknologi informasi dalam operasional UMKM dapat memberikan dampak positif terhadap produktivitas dan efisiensi bisnis, serta memberikan solusi praktis kepada UMKM untuk mengatasi tantangan operasional sehari-hari.